Authentic Assessment, Teacher Pedagogy, and Student Satisfaction - Keai Lim (Basic and Applied Education Research Journal, 2022)
This article purposed to analyse the mediating role of authentic assessment in the relationship between teaching pedagogy and student satisfaction in the Singapore Private Education industry. The target group for this quantitative study consisted of international Postgraduate MBA students from various countries selected through simple random sampling methods. A questionnaire consisting of three dimensions i.e. Student Satisfaction, Teaching Pedagogy, and Authentic Assessment was constructed and used to collect opinions from 344 MBA graduates. Statistical Package for the Social Sciences (SPSS) was used to analyse the collected data. Multiple Linear Regression Analysis and Sobel Test showed the mediating effect and the predictive power of authentic assessment on the relationship between Teaching Pedagogy and student satisfaction. Essential research ethical issues were addressed and adhered to. The findings and knowledge generated from this study on student satisfaction will be significant and beneficial for institutions or individuals to identify and rectify any area for improvement in student satisfaction.